Maturity levels of material cycles and waste management in a context of green supply chain management: an innovative framework and its application to Brazilian cases - Ferreira, Marco Antonio; Jabbour, Charbel Jose Chiappetta [UNESP]; de Sousa Jabbour, Ana Beatriz Lopes [UNESP] (Springer Nature, 2017)
The objective of this study is to identify the relationship between the maturity of environmental management and the adoption of green supply chain management (GSCM) practices utilizing an integrative framework and evidence from multiple cases. To achieve this goal, a state of the art literature review on environmental management maturity was performed, and a typology of GSCM practices was created to produce an original integrative framework of GSCM maturity levels. To verify its applicability to real cases, five companies in supply chains with high levels of environmental impact were analyzed. Of the five companies, two were in the battery business, two in the pesticides business, and one in the automotive business. Adherence to the integrative framework was verified, and sensitivity to changes in maturity of environmental management and the adoption of GSCM practices were observed, achieving the research’s objective. The following classification of GSCM maturity levels was obtained: (a) first, the reactive GSCM level with low adoption of GSCM practices, which is motivated by legal restrictions; (b) second, the preventive GSCM level with average adoption of GSCM practices, which is driven by cost reduction; (c) and third, the proactive GSCM level, which is driven by the pursuit of competitive advantages.
Keywords: Brazil; Green supply chain management practices; Sustainable operations management; Sustainable supply chain; Waste management